Recent Development in Wireless Sensor and Ad-hoc Networks - Patnaik, Srikanta; Li, Xiaolong; Yang, Yeon-Mo (Signals and Communication Technology,, 2015)
Wireless Sensor Network (WSN) consists of numerous physically distributed autonomous devices used for sensing and monitoring the physical and/or environmental conditions. A WSN uses a gateway that provides wireless connectivity to the wired world as well as distributed networks. There are many open problems related to Ad-Hoc networks and its applications. Looking at the expansion of the cellular infrastructure, Ad-Hoc network may be acting as the basis of the 4th generation wireless technology with the new paradigm of 'anytime, anywhere communications'. To realize this, the real challenge would be the security, authorization and management issues of the large scale WSNs. This book is an edited volume in the broad area of WSNs. The book covers various chapters like Multi-Channel Wireless Sensor Networks, its Coverage, Connectivity as well as Deployment. It covers comparison of various communication protocols and algorithms such as MANNET, ODMRP and ADMR Protocols for Ad hoc Multicasting, Location Based Coordinated Routing Protocol and other Token based group local mutual exclusion Algorithms. The book also covers a chapter on Extended Ad hoc On-Demand Distance Vector (EAODV) routing protocol based on Distributed Minimum Transmission Multicast Routing (DMTMR). One chapter is dedicated to OCDMA and its future application and another chapter covers development of Home Automation System using SWN.